Single-Stage Continent Reconstruction of Composite Pericommissural Defects Using a Combination of Pacman-Style Free Radial Forearm Flaps and Modified Elastic Musculomucosal Flaps - Balakrishnan, T.M.; Aruna, M.; Christabel, Prethee Martina; Jaganmohan, J. (Indian Journal of Plastic Surgery, 2022)
Introduction Based on the cross-innervation of buccal and marginal mandibular branches of the facial nerve, oblique elastic musculomucosal flaps (OEMMFs) can be harvested and used for continent neo-commissure and modiolus reconstructions. The composite pericommissural defects can then be reconstructed with double cutaneous paddles in Pacman-style free radial forearm flap (PFRFF). This novel single-stage continent reconstruction of composite post-excisional commissure and pericommissural (CPECPC) defects is evaluated in this study.Patients and Methods This retrospective cohort study was conducted from April 2016 to March 2019. Forty-two patients underwent this type of reconstruction using a combination of PFRFF and OEMMF for the CPECPC defects. They were followed for an average period of 11.5 months. At the end of the follow-up period, they were assessed using the objective institutional scoring system by two independent observers and final score was computed for each patient.Results The average score obtained at the end of the follow-up period was 11.5 (p = 0.035) using the institutional assessment scoring system, which evaluated both the overall aesthesis and function of the neo-commissure and modiolus.Conclusions The combination of OEMMF and PFRRF for the single-stage reconstruction of CPECPC defects is a useful addendum for re-establishing the aesthesis and continence at the reconstructed site.
Keywords: Pacman-style free radial forearm flaps; oblique elastic musculomucosal flaps; oral commissure reconstruction; oral continence